Research on the Application of Machine Vision in Industrial Robots - Li, Zeda (Exploring Science Academic Conference Series, 2026)
With the rapid development of intelligent manufacturing and Industry 4.0, industrial robots have been widely applied in modern manufacturing processes. However, traditional industrial robots often rely on pre - programmed instructions and fixed trajectories, which limit their flexibility and adaptability in complex environments. Machine vision technology enables industrial robots to perceive, identify, and analyse surrounding objects through image acquisition and processing. This paper systematically studies the application of machine vision in industrial robots. First, the basic concepts, components, working principles, and image processing technologies of machine vision are introduced. The structure and operating principles of industrial robot systems are then analysed. Furthermore, several typical applications of machine vision in industrial robots are discussed, including workpiece identification and positioning, visual guidance in welding and assembly, product quality inspection, and automatic sorting systems. In addition, the current challenges in machine vision technology, including environmental interference, target occlusion, high hardware costs, and real-time processing requirements, are analysed. Finally, future development trends are explored, including the integration of artificial intelligence, multi -sensor fusion, digital twins, and intelligent manufacturing systems. The study shows that machine vision plays an important role in improving the accuracy, efficiency, and automation level of industrial robots and will continue to promote the intelligent development of modern manufacturing.